Principles and labs for fitness & wellness - Hoeger, Werner W. K.; Hoeger, Sharon A.; Fawson, Amber L.; Hoeger, Cherie I. (Cengage Learning, 2018)
In addition to a thorough discussion on physical fitness, including all health- skill-related components, extensive and up-to-date information is provided on behavior modification, nutrition, weight management, cardio vascular and cancer risk reduction as well as exercise and aging. Furthermore, the information has been written to provide the necessary tools and guidelines for lifetime exercise and a wellness way of life.